2005
DOI: 10.1189/jlb.0904541
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic activity of the polysaccharide chitosan at lymphoid tissues after oral administration

Abstract: Chitosan is a cationic polysaccharide derived from the partial deacetylation of chitin, which exhibits particular properties: interacts with negatively charged sites on the cell surface; changes the permeability of intestinal epithelium, enhancing the uptake of peptides and proteins; and activates leukocytes. Antigens coadministered or encapsulated with the polysaccharide show improved mucosal and systemic humoral immune responses, although the mechanism is poorly understood. Herein, we characterized in Peyer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 55 publications
(91 reference statements)
5
74
0
Order By: Relevance
“…Furthermore, mature DCs also acquire their ability to activate T cells (Banchereau et al, 2000;Mellman & Steinman, 2001). It was shown that chitosan increased DCs maturation (Porporatto et al, 2005), but some studies reported that chitosan has no effect on DCs (Bivas-Benita et al, 2004;Wischke, Borchert, Zimmermann, Siebenbrodt, & Lorenzen, 2006). Our results demonstrated that B-COS treatment enhanced the surface expressions of CD86 and MHCII on SDCs, rather than TLR4 siRNA-transfected SDCs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, mature DCs also acquire their ability to activate T cells (Banchereau et al, 2000;Mellman & Steinman, 2001). It was shown that chitosan increased DCs maturation (Porporatto et al, 2005), but some studies reported that chitosan has no effect on DCs (Bivas-Benita et al, 2004;Wischke, Borchert, Zimmermann, Siebenbrodt, & Lorenzen, 2006). Our results demonstrated that B-COS treatment enhanced the surface expressions of CD86 and MHCII on SDCs, rather than TLR4 siRNA-transfected SDCs.…”
Section: Discussionsupporting
confidence: 52%
“…Chitosan is the deacetylated derivative of chitin, and previous works revealed that chitosan plays a role in immune responses for plant and animal cells (Porporatto, Bianco, & Correa, 2005;Villiers et al, 2009). Chitosan oligosaccharide (Chitooligosaccharides, COS), derived from chitosan by enzymatic hydrolysis (Zhang, Du, Yu, Mitsutomi, & Aiba, 1999), is a new kind of biofunctional material which exhibits improved biological activities when compared with chitosan (Cho et al, 2008;Moon et al, 2007;Nam, Kim & Shon, 2007;PalmaGuerrero, Jansson, Salinas, & Lopez-Llorca, 2008;Rahman et al, 2008;Yoon, Moon, Park, Im, & Kim, 2007), such as inhibiting growth of bacteria and fungi, exerting anti-tumor activity, and acting as immunopotentiating effectors.…”
Section: Introductionmentioning
confidence: 99%
“…Porporatto et al observed that a dose of 1 mg chitosan had no significant effect, while a single dose of 3 mg stimulated the expression of IL-10 in mononuclear cells of rats fed (Porporatto et al, 2005 (Ueno et al, 2001). …”
Section: In Vivo Toxicity Of Chitosanmentioning
confidence: 99%
“…It was reported that the strong stimulatory activity of chitosan has been mainly attributed to the N-acetyl-d-glucosamine residues and its effect could be mediated by combined action with a macrophage mannose specific receptor (Porporatto et al 2003;Feng et al 2004). Zhao (2004) indicated that macrophages activated by oligochitosan in- Porporatto et al (2005) found that chitosan could be absorbed by the antigen-presenting cells and profoundly affected immunity by activating the T cell in the intestinal mucosa of rats. Although its mechanism of action is not entirely clear, the NO production in this study may be associated with increase of iNOS activity in the serum and iNOS mRNA expression in the small intestine of piglet by chitosan.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al (2008) indicated that chitosan might enhance the doi: 10.17221/8405-CJAS cell-mediated immune response in early-weaned piglets by modulating the production of cytokines and antibodies. Porporatto et al (2005) found that the uptake of chitosan involved the antigenpresenting cells in the intestinal of rats after oral administration, and this mucoadhesive polysaccharide profoundly affected intestinal immunity by enhancing the T helper cell type 2 (Th2)/Th3 microenvironment in the mucosa. Li et al (2009) found that dietary supplementation with chitosan enhanced immune functions which were associated with the increase of nitric oxide (NO) secretion and inducible nitric oxide synthase (iNOS) mRNA expression in the small intestine of broilers.…”
Section: Introductionmentioning
confidence: 99%